Plagioclasites from chromite-bearing ultramafic rocks of the Rai-Iz massif - N. V. Vakhrusheva; K. S. Ivanov; A. E. Stepanov; S. P. Shokalsky; A. N. Azanov; V. V. Hiller; P. B. Shiryayev (Литосфера, 2016)
The corundum-bearing and without-corundum plagioclasites from chromite-bearing ultramafic rocks of Rai-Iz massif were studied. Chemical composition of the rock-forming minerals and rock geochemical characteristics was determined. The U-Pb zircon dating (using SHRIMP-II microprobe) of plagioclasites yielded an age of 398 ± 3 and 404.4 ± 2.8 Ma - Lower-Middle Devonian boundary. At that time on the background of powerful collision it occurred a deep metamorphic processing of Rai-Iz ultramafic rocks resulting in forming of high-chromium chromite ore and separation of vein-series represented by substantially plagioclase rocks with corundum (ruby) mineralization.